Pesantren Curriculum Management Based On Religious Moderation At Mahad Al Jamiah - Ahmad Fikri; Muhammad Munawir Pohan; Khairul Anwar (At-Tarbiyat, 2023)
This study attempts to provide light on the administration of a pesantren curriculum based on religious moderation at Mahad Al Jamiah, Kerinci State Islamic Institute, Jambi Province. This study is categorised as qualitative research using a case study methodology. Eight participants made up the informant group for this study, including Mudir Mahad, the teaching staff, and six Mahad students. Purposive sampling was used to choose the informants. The researcher himself serves as the study's instrument. This study used observation, interviews, and documentation studies as data collection methods. Observation of the development, carrying out, and evaluation of a curriculum in the form of a checklist sheet. Semi-structured interviews were the appropriate category for the user interviews. Data and papers that are linked to the research issue serve as documentation. Nvivo Plus version 11 software was utilised for all data entry, coding, exploration, visualisation, and presentation procedures in this investigation. Tests for credibility, dependability, and confirmability can be used to determine the authenticity of the data. The findings demonstrated that curriculum development was carefully planned, that curriculum implementation proceeded smoothly, and that curriculum evaluation was done in collaboration with the Quality Assurance Agency.